Treatment of chronic hepatitis C in haemophilic patients with interferon and ribavirin: a meta-analysis - Franchini, Massimo; Mengoli, Carlo; Veneri, Dino; Mazzi, Romualdo; Lippi, Giuseppe; Cruciani, Mario (Journal of antimicrobial chemotherapy, 2008)
Hepatitis C virus (HCV) infection is a major cause of morbidity and mortality among haemophilic patients who were treated with clotting factor concentrates before the availability of virus-inactivated factors in the mid 1980s. In order to analyse the effect of the current combination anti-HCV treatment [i.e. ribavirin plus interferon (IFN)] in this subset of HCV-infected patients, we performed a systematic review with meta-analysis of the available literature. The outcome was sustained viral suppression. When trials included for the main predictors two arms (positive and negative), the effect size was described as a comparative index [odds ratio (OR)] and a standard meta-analytical procedure was applied. However, when trials did not report the outcome in separate study arms, the effect size was a non-comparative index (success rate) and comparisons between predictor-positive and -negative studies were performed by meta-regression. Data involving 824 haemophilic HCV-infected patients treated with IFN plus ribavirin were collected from 18 articles (14 prospective cohort studies, 1 retrospective study and 3 randomized controlled trials). The higher rate of sustained viral response was observed in human immunodeficiency virus (HIV)-negative naive haemophiliacs treated with pegylated-IFN in combination with ribavirin (61%, ranging from 45% for genotype 1 to 79% for non-1 genotypes). Genotype 1 (OR, 0.15; 95% CI, 0.09-0.25) and co-infection with HIV (OR, 0.25; 95% CI, 0.08-0.81) were strong predictors of worse response to IFN therapy. Our meta-analysis shows that the pattern of response to combination anti-HCV therapy of chronically HCV-infected haemophiliacs is similar to that achieved in the general HCV-infected population.